Phase breaking in three-terminal contacted single-walled carbon nanotube bundles - KRSTIC, VOJISLAV (The American Physical Society, 2000)
The three-terminal electrical transport through single-walled carbon nanotube bundles with low resistive metal contacts is investigated at room temperature. After correcting for the lead resistance, two-probe resistances close to the value expected for a metallic single-walled carbon nanotube are found. Analysis of the experimental data in the frame of the Landauer-Bu?ttiker formalism reveals the phase- and momentumrandomizing effect of the third electrode, which is at floating potential, on the quasiballistic transport. Within this model, the phase-coherence length of the charge carriers is estimated to be '300 nm at room temperature.
PUBLISHED
Keywords: Physics